2014
DOI: 10.1080/15017419.2014.972447
|View full text |Cite
|
Sign up to set email alerts
|

Planning individually? Spotting international welfare trends in the field of rehabilitation in Norway

Abstract: International welfare trends are sweeping across the western world and have gained a lot of attention from researchers. However, few contributions have demonstrated the practical effects of these trends. This article will illustrate this using the individual plan as a case showing that some unintended forms of use can be regarded as traces of international welfare policy trends, and are not in line with the original ideologically based intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The software's search function (QSR International Pty Ltd 1999-2014, 2014) was often applied to the entire text to seek words or sentences that could be related to the codes we were using.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The software's search function (QSR International Pty Ltd 1999-2014, 2014) was often applied to the entire text to seek words or sentences that could be related to the codes we were using.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past decade, several new groups have been defined Research within the disability and mental health fields shows increased collaboration and user participation (Breimo, 2014;Michaelsen, Vatne, & Hollingen, 2011). Cancer research shows that formal caregivers do not practice IP, and three barriers to IP are identified: a) formal caregivers' knowledge about their duty to inform and facilitate IP, b) formal caregivers' knowledge about collaboration networks within care, and c) allocation of time to perform the necessary administrative work (Saegrov, 2015).…”
Section: Individual Planmentioning
confidence: 99%
“…Alongside the introduction of activation policies, Norwegian social workers have argued for an empowering rather than a coercive approach (Andreassen, 2019;Hansen & Natland, 2017) with a growing interest in person-centred interventions such as developing individual plans for social service users (Breimo, 2016). In vocational follow-up, person-centred supported employment (Bonfils et al, 2017; European Union of Supported Employment, 2010) is offered to some groups of jobseekers, with immigrant jobseekers most recently included as recipients of this type of intervention (Maximova-Mentzoni, 2019).…”
Section: The Norwegian Contextmentioning
confidence: 99%
“…Several researchers have studied how different guidelines and procedures not only organise the lives of the service users, but of the work of social workers as well. Social workers are expected to follow and use, for example, risk reduction strategies in child protection work (Brown 2006) and child custody planning procedures (Kushner 2006), make individual rehabilitation plans (Breimo 2016) or assess who can qualify to be foster carers or adoptive parents (Hicks 2009). These studies show that IE offers a framework to analyse the connections between work with individual service users, the organisational contexts of work and its guiding principles.…”
Section: The Value Of Institutional Ethnography For Social Work Researchmentioning
confidence: 99%